Analisis Faktor-Faktor Yang Memengaruhi Customer Loyalty - Effendi, Hernita; Yenita, Yenita (Widya Cipta: Jurnal Sekretari dan Manajemen, 2023)
Peningkatan jumlah penumpang Terminal Jatijajar Depok hanya terjadi pada peak season seperti: perayaan Natal, pergantian tahun, dan hari raya besar, namun di bulan-bulan lainnya nampak fluktuatif dan cenderung turun. Penelitian bertujuan untuk mengkaji faktor-faktor yang memengaruhi customer loyalty Terminal Jatijajar Depok. Penelitian termasuk dalam deskriptif kuantitatif. Data dianalisis menggunakan path analysis. Hasil membuktikan service quality tidak memengaruhi customer satisfaction and loyalty, tetapi berpengaruh pada customer trust. Customer experience tidak memengaruhi customer satisfaction and trust, tetapi mampu memengaruhi customer loyalty. Satisfaction tidak mampu memengaruhi customer loyalty. Trust memengaruhi customer loyalty. Service quality tidak memengaruhi loyalty dimediasi customer trust and satisfaction, tetapi customer experience mampu memengaruhi. The increase in passengers at the Jatijajar Depok Terminal only occurred during the peak season such as: Christmas celebrations, New Year's Eve, and major holidays, but in other months it seemed fluctuating and tended to decrease. The research will aim to examine the factors that influence loyalty. Research is included in the quantitative descriptive. Data analysis using path analysis. The results prove that service quality does not affect customer satisfaction and loyalty, but does affect customer trust. Customer experience does not affect customer trust and satisfaction, but can influence customer loyalty. Satisfaction is not able to influence customer loyalty. Trust affects customer loyalty. Service quality does not affect loyalty mediated by customer trust and satisfaction, but customer experience can influence it.